Activity of Cathelicidin Peptides against Simkania negevensis. (24th February 2011) - Donati, Manuela; Di Francesco, Antonietta; Di Paolo, Maria; Fiani, Natascia; Benincasa, Monica; Gennaro, Renato; Nardini, Paola; Foschi, Claudio; Cevenini, Roberto
Abstract : The in vitro activity of six cathelicidin peptides against the reference strain Z of Simkania negevensis was investigated. Five peptides—PG-1, Bac7, SMAP-29, BMAP-27, and BMAP-28—proved to be active at very low concentrations (1 to 0.1  μ g/mL), while LL-37 cathelicidin was ineffective even at a concentration of 100  μ g/mL. In comparison to chlamydiae, S. negevensis proved to be more susceptible to the antimicrobial peptides tested.